Ginsenoside Rb1 can ameliorate the key inflammatory cytokines TNF-α and IL-6 in a cancer cachexia mouse model - Shuai Lu; Yubo Zhang; Huajun Li; Jing Zhang; Yingqian Ci; Mei Han (BMC, 2020)
Abstract Background Cancer cachexia is a severe condition that leads to the death of advanced cancer patients, and approximately 50~80% of cancer patients have cancer cachexia. Ginseng extract has been reported to have substantial anticancer and immune-enhancing effects; however, no study has reported the use of ginseng alone to treat cancer cachexia. Our study's purpose was to investigate the therapeutic effects of ginseng-related monomers or mixtures on a cancer cachexia mouse model. Methods We selected BALB/c mice and injected the mice subcutaneously with C26 colon cancer cells to construct a cancer cachexia experimental animal model. The water extract of ginseng (WEG), two types of ginseng extracts (ginsenosides at doses of 5 mg/kg (GE5) and 50 mg/kg (GE50)) and ginsenoside Rb1 (Rb1) were used to treat cancer cachexia mice. Enzyme-linked immunosorbent assays (ELISAs) were used to analyze the inhibitory effects on two key inflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6). Results Our experimental results show that GE5, GE50 and Rb1 significantly reduced the levels of TNF-α (P < 0.01) and IL-6 (P < 0.01), which are closely related to cancer cachexia; however, WEG, GE5, GE50 and Rb1 did not significantly improve the gastrocnemius muscle weight or the epididymal fat weight of mice with cancer cachexia. Conclusions These results indicate that GE5, GE50 and Rb1 may be useful for reducing symptoms due to inflammation by reducing the TNF-α and IL-6 cytokine levels in cancer cachexia mice, thereby ameliorating the symptoms of cancer cachexia. Our results may be beneficial for future studies on the use of Chinese herbal medicines to treat cancer cachexia.